Classificação do café beneficiado: uma proposta para pagamento pela qualidade dos grãos - Santos, Fabio Lyrio (Universidade Federal de São Carlos, 2012)
Brazil is the largest world coffee producer and exporter. The crop arrived in the country in the colonial period, in the mid-seventeenth century, and during much of the nineteenth and twentieth centuries was the Brazilian main export product. Brazil produces coffees of different qualities. In raw grain status, the product is traded after being benefited in the farms or cooperatives of farmers. Each lot of green coffee receives a respective commercial description according to the Brazilian official classification. This instrument coordinates the product domestic market serving as orientation for the pricing on transactions and hence for the remuneration of farmers and cooperatives. The problem is that the classification is based mainly on the type indicator, which is a quantifier of physical defects observed in the samples. Thus, the real quality of the beans is underprivileged, generating uncertainty in transactions, opportunism, and problems of adverse selection, also hindering the grower to earn income by quality. The research studied the triple inter-relationship between the classification system, the quality attributes required by industry and the payment to the grower. Thirteen stakeholders of the production chain comprised the object of study: five cooperatives located in the main Brazilian coffee regions, five roasters associated with them, and three intermediary companies (traders) located in the region of Hamburg, Germany. The studied cases showed that the problem is partially solved by the cooperatives through the use of alternative classification systems. These systems provide fairer remuneration to the grower and better highlight the qualities of the lots to their customers (intermediaries or industry). The restructuring of the classification system, therefore, appears to be potentially able to redirect the payment system and to bring economic benefit to the productive sector. In the results the research presents a proposal of classification system for green coffee, built from the empirical data.
Keywords: Engenharia de produção; Café - mercado; Agribusiness; Governança; Sistema de classificação; Qualidade; Pagamento por qualidade; Coffee; Classification system; Quality; Payment for quality; Agribusiness; ENGENHARIAS::ENGENHARIA DE PRODUCAO